Factors affecting Generation Z tourist visit intention in Nanchang Jiangxi province, China: Attitude towards short videos as a mediator - Huimin, Xie; Karim, Rosman Bin; Azman, Norhidayah Binti (Edelweiss Applied Science and Technology, 2025)
In the era of rapid digitalization and advancements in information technology, short video platforms have become a crucial medium for marketing tourism destinations, significantly influencing tourists’ perceptions and decision-making processes. This study explores the impact of short video quality factors (perceived trustworthiness, perceived enjoyment, perceived usefulness, and perceived ease of use) on tourists’ intention to visit and examines the mediating role of tourists’ attitudes toward short videos in this process. A conceptual model was developed to investigate the relationships, and a quantitative research approach was adopted, employing a structured questionnaire to collect data among Generation Z individuals, particularly university students aged 19 to 24 from thirteen public universities in Nanchang, Jiangxi Province. The population of the study is 150,000, with a simple random sampling technique. The data were analyzed using SPSS and AMOS statistical programs. The findings reveal that short video quality factors have a significant direct impact on tourists’ intention to visit, while tourists’ attitudes toward short videos play a crucial mediating role. This indicates that a positive attitude not only directly boosts visit intention but also amplifies the influence of short video content factors. This study recommends that tourism destination managers and marketers focus on enhancing the trustworthiness, enjoyment, usefulness, and ease of use of short video content to effectively attract and engage Generation Z tourists.